Capabilities of interventional radiology in the treatment of portal vein stenosis after pediatric liver transplantation - A. V. Semenkov; N. A. Koroteyeva; T. M. Ashuba; Yu. R. Kamalov; V. V. Khovrin; D. S. Burmistrov; A. A. Bogdanov-Berezovsky; S. A. Abugov (Трансплантология (Москва))
The paper describes 2 cases of correction of portal vein stenosis after pediatric liver transplantation using interventional radiology techniques. Its long-term result is analyzed. X-ray endovascular correction of portal vein stenosis after left lateral liver bisegment transplantation demonstrates a high clinical efficiency, yielding good long-term results.